Impact of spastic cerebral palsy upon the quality of life of children under the age of 12 years in Erbil City: parents’ reports - hasan, Shukir; Shaker, Norhan; ismail, Zhian (Iraqi National Journal of Nursing Specialties, 2015)
Objectives: This study aims to assess the quality of life of cerebral palsy children less than 12 years old reported byparents in Erbil city/Iraq.Methodology: A descriptive study was conducted during 2014, to describe the quality of life of cerebral palsychildren. One hundred mothers have cerebral palsy children were participated in this study. The study took place atHelena Center for handicapped children in Erbil City. Questionnaire was used to collect data, which consists of twomain parts. The first part is divided into two sections; section one was described the mothers’ demographiccharacteristics, while the second section was for identifying the demographical characteristics of cerebral palsychildren. The inventory trademark" (PedsQLTM) 3.0 (parents' reports) was used in second part of the questionnaire.Statistical Package for Social Science (SPSS) version 18 was used to analyze date. Chi-squared test was applied tofind out the association and significance.Results: Most of the mothers were from low socioeconomic status, living in urban areas and aged between 28-37years old. Majority of cerebral palsy children were male, aged between 2 - 4 and diagnosed with spastic type. Thesignificant associations were found between types of cerebral palsy and daily activities, pain and hurt, speech andcommunication and eating and activities respectively at p-value 0.032, 0.000, 0.011, and 0.014.Recommendations: The study recommended special health educational programs for mothers to improve the qualityof life of their cerebral palsy children